ANALISIS KEPUASAN KONSUMEN MOBIL TOYOTA KIJANG INNOVA DI KOTA BANDAR LAMPUNG - Theresia Dhian Kusumawati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
Currently the products of Automotive has developed very rapidly as a result of the demandsof the market. One of the automotive products undergo rigorous competition is a car. Car is one ofthe needs or means used by consumers. This condition makes manufacturers trying with each otherto market similar products with different quality and brand from its competitors. Toyota is a brand ofautomotive is traded on the market.This study aims to determine how much influence the Product Quality Perception and BrandReputation of the Customer Satisfaction. The results on the variables obtained coefficient ofdetermination (R2) of 0.695 indicates that Customer Satisfaction are influenced by the perceivedproduct quality and Brand Reputation at 69.5% while the remaining 30.5% is influenced by factorsother than the factors examined.